ANALYSIS OF YOUTH PERCEPTIONS OF THE AGRICULTURAL SECTOR IN DETUSOKO DISTRICT, ENDE DISTRICT: SEM-PLS APPROACH - Daniel Simo; Cakti Indra Gunawan; T. Budi Santoso (RADJA PUBLIKA, 2023)
This research has important meaning in the context of agricultural development and farmer regeneration in NTT. The findings of this research can provide valuable insights for regulators and stakeholders in designing appropriate policies to increase the younger generation's interest in agriculture and ensure the sustainability of an independent and sustainable agricultural sector in the region. The sampling technique used was Simple Random Sampling, with a sample size of 125 people from a youth population of 1,040 people, with a tolerance limit of 12%. This study seeks to identify factors influencing youth perceptions of agriculture in the region and will use data analysis to support its findings. Data collection methods include interviews, observation, questionnaires and documentation. The collected data will be analyzed using quantitative descriptive methods. The analysis tool of choice is Partial Least Square-Structural Equation Modeling (PLS-SEM) which is assisted by WrapPLS 7.0 software. PLS analysis aims to identify factors that influence youth perceptions of agriculture. The research results show that Social Status, Income, Land Area, Education, and Age have a positive and significant influence on youth perceptions of agriculture in the region. This means that these factors influence the way the younger generation views and responds to agricultural issues in their environment.